2016
DOI: 10.1136/openhrt-2016-000478
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is associated with delirium and mortality after transcatheter aortic valve implantation

Abstract: ObjectiveWe hypothesised that frailty assessment is of additional value to predict delirium and mortality after transcatheter aortic valve implantation (TAVI).MethodsObservational study in 89 consecutive patients who underwent TAVI. Inclusion from November 2012 to February 2014, follow-up until April 2014. Measurement of the association of variables from frailty assessment and cardiological assessment with delirium and mortality after TAVI, respectively.ResultsIncidence of delirium after TAVI: 25/89 (28%). Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 30 publications
9
68
1
2
Order By: Relevance
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
“…When inclusion and exclusion criteria were applied, 31 publications remained for assessment. 6,8,9,11,17, Most included studies were observational (14 prospective, 6,17,23,[26][27][28][29][30]33,35,37,41,44,47 6 propensity matched, 22,24,25,36,40,42 10 retrospective 8,9,11,31,32,34,38,43,45,46 ), with only one randomized controlled trial. 39 Differences in the differential diagnosis between POD and other comparable cognitive disorders, including dementia, depression, and schizophrenia, are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations